Structural Analysis and Involvement in Plant Innate Immunity of Xanthomonas axonopodis pv. citri Lipopolysaccharide - Casabuono, Adriana (American Society for Biochemistry and Molecular Biology, 2011)
Xanthomonas axonopodis pv. citri (Xac) causes citrus canker, provoking defoliation and premature fruit drop with concomitant economical damage. In plant pathogenic bacteria, lipopolysaccharides are important virulence factors, and they are being increasingly recognized as major pathogen-associated molecular patterns for plants. In general, three domains are recognized in a lipopolysaccharide: the hydrophobic lipid A, the hydrophilic O-antigen polysaccharide, and the core oligosaccharide, connecting lipid A and O-antigen. In this work, we have determined the structure of purified lipopolysaccharides obtained from Xanthomonas axonopodis pv. citri wild type and a mutant of the O-antigen ABC transporter encoded by the wzt gene. High pH anion exchange chromatography and matrix-assisted laser desorption/ionization mass spectrum analysis were performed, enabling determination of the structure not only of the released oligosaccharides and lipid A moieties but also the intact lipopolysaccharides. The results demonstrate that Xac wild type and Xacwzt LPSs are composed mainly of a penta- or tetra-acylated diglucosamine backbone attached to either two pyrophosphorylethanolamine groups or to one pyrophosphorylethanolamine group and one phosphorylethanolamine group. The core region consists of a branched oligosaccharide formed by Kdo(2)Hex(6)GalA(3)Fuc3NAcRha(4) and two phosphate groups. As expected, the presence of a rhamnose homo-oligosaccharide as O-antigen was determined only in the Xac wild type lipopolysaccharide. In addition, we have examined how lipopolysaccharides from Xac function in the pathogenesis process. We analyzed the response of the different lipopolysaccharides during the stomata aperture closure cycle, the callose deposition, the expression of defense-related genes, and reactive oxygen species production in citrus leaves, suggesting a functional role of the O-antigen from Xac lipopolysaccharides in the basal response.